Expression and purification of truncated diphtheria toxin, DT386, in Escherichia coli: An attempt for production of a new vaccine against diphtheria - Fatemeh Shafiee; Mohammad Rabbani; Mahdi Behdani; Ali Jahanian-Najafabadi (Wolters Kluwer Medknow Publications, 2016)
The aim of this study was to produce a recombinant protein consisting of the catalytic and translocation domains of diphtheria toxin for its later application as a vaccine candidate against Corynebacterium diphtheria. To achieve this goal, at first, the amino acid sequence of DT386 was used for prediction of T and B cell epitopes using on-line servers. The DT386 coding sequence was synthesized and subcloned into the NcoI and XhoI sites of pET28a plasmid and recombinant pET28a plasmid was used to transform Escherichia coli BL21 (DE3) host cells. Afterwards, recombinant cells were selected and subjected to induction of expression by 1 mM isopropyl β-D-1-thiogalactopyranoside, (IPTG). Expression of the desired protein was evaluated by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and Western blotting, and finally, the recombinant protein was purified using nickel affinity chromatography. The results of epitope prediction using on-line servers established the ability of DT386 for stimulation of immune system against diphtheria toxin. Restriction digestion of the recombinant plasmids using NcoI and XhoI enzymes confirmed the fidelity of cloning by producing a band of about 1200 bp. SDS-PAGE analysis following induction of expression and also purification step confirmed the expression of the desired protein by showing a band of about 45 kDa. In addition, Western blot analysis using anti-6X-His antibody confirmed the identity of the expected protein. In conclusion, in the present study we amplified and cloned the coding sequence of DT386 fragment, followed by its expression by E. coli BL21 (DE3) cells. Then, the expressed protein was purified and will be used for later studies of evaluation of its immunogenic properties.